TRADISI LOKAL MASYARAKAT DALAM PENGELOLAAN KAWASAN KONSERVASI PULAU YAMDENA KABUPATEN MALUKU TENGGARA BARAT - Nanlohy, Hellen; Timisela, Natelda R; Estradivari, Estradivari (Program Studi Agrobisnis Perikanan, Universitas Pattimura, 2019)
West Southeast Maluku Regency is one of the districts in Maluku Province. This regency has several large and small islands. One of the big islands is Yamdena Island. This island has been designated by the government as a water conservation area. This area is an important area for several marine species such as turtles, dugongs, whales and dolphins and plays an important role in the ecological connectivity of waters through local governance. The purpose of this study is to describe local traditions in the management of territorial waters in the Yamdena Island conservation area. The method used is a social survey method. The approach adopted was focus group discussions and key informant interviews. The analysis used is descriptive qualitative. This research shows that some villages still apply local traditions, namely sasi teripang and kima. Another tradition is the existence of prohibitions and sanctions in the management of marine resources made orally by the village government along with traditional institutions and local organizations. This local tradition was made since ancestors and is still ongoing to this day as a form of conservation of marine resources in order to remain sustainable and sustainable.